Anodic formation of AgI oxide on Ag-Au alloys - Grushevskaya, Svetlana (Array, 2008)
Abstract: The kinetics of anodic dissolution of silver and Ag-Au alloys (xAu = 0.1–30 %) in aqueous alkaline solution under the conditions of AgI oxide formation has been examined. Using the techniques of cyclic voltammetry and chronoamperometry it has been established that Ag2O anodic formation and cathodic reduction on silver and on alloys of all compositions under review are controlled by Ag+ cation migration in the oxide layer. The oxide film consists of a thin inner layer (apparently AgOH) and of a thicker outer layer Ag2O. These layers slightly differ in specific electro-conductivity. Using the photopotential measurements it has been shown that Ag2O oxide is an n-type semiconductor with an excess of silver atoms. The AgI oxide layer formed on monocrystalline Ag(111) is more stoichiometric than the layer formed on polycrystalline Ag